Introduction to laser science and engineering - Taylor, Travis S. (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2020)
"Introduction to Laser Science and Engineering provides a modern resource for a first course in lasers for both students and professionals. Starting from simple descriptions, this text builds upon them to give a detailed modern physical understanding of the concepts behind light, optical beams and lasers. The coverage starts with the nature of light and the principles of photon absorption and transmission, leading to the amplified and stimulated emission principals governing lasers. The specifics of lasers and their application, safe use and future prospects are then covered, with a wealth of illustrations to provide readers with a visual sense of optical and laser principles"--
What is light? -- The classical description of light -- The mathematical era begins -- What is amplification? -- Amplifier basics -- Multiple amplifiers -- What is the stimulated emission of radiation? -- The Bohr model of the atom -- Absorption, stimulated emission, and spontaneous emission -- A more realistic model -- What are lasers? -- Laser basics -- The rate equation -- The cavity -- What are some types of lasers? -- Solid-state lasers -- Dye lasers -- Semiconductor lasers -- Gas lasers -- Chemical lasers -- Metal vapor lasers -- Ion lasers -- More exotic lasers -- How do we describe lasers? -- Continuous wave or pulsed -- Laser modes -- Spectral content -- Collimation, divergence, beam expansion, and beam reduction -- Output energy, power, irradiance, and beam quality -- Efficiency -- How do we use lasers safely? -- The laser safety basics -- Types of injuries possible from laser beams -- Other safety considerations with laser systems -- Practical safety considerations -- What are some laser applications? -- Lasers used in experiments -- Lasers in the field -- High energy lasers -- Some other applications.
OCLC-licensed vendor bibliographic record.
Keywords: Lasers; TECHNOLOGY / Engineering / Civil